2012
DOI: 10.1016/j.acra.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sensitivity of a Pre-MRI Questionnaire and Point of Care eGFR Testing for Detection of Impaired Renal Function

Abstract: Rationale and Objectives The Food and Drug Administration recommends renal function estimation using laboratory testing for patients at risk for chronically reduced kidney function before the administration of gadolinium-based contrast agents (GBCAs). Point-of-care (POC) estimated glomerular filtration rate (eGFR) testing was added to the pre-magnetic resonance (MR) questionnaire at our institution in June 2008 for all patients undergoing a contrast-enhanced MR exam. This study was done to evaluate the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Observational studies have shown that these questionnaires can identify patients with eGFR < 45 ml/min/1.73 m 2 with adequate sensitivity, especially if they are aged less than 70 [ 9 11 ]. Since eGFR measurement can detect more patients with renal dysfunction than questionnaires [ 12 ], with easier patient logistics and similar cost-effectiveness [ 13 , 14 ], many hospitals have adopted a policy of sCr measurements in all patients scheduled for intravenous (IV) CM and no longer use questionnaires for risk stratification or selection for eGFR measurement (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Observational studies have shown that these questionnaires can identify patients with eGFR < 45 ml/min/1.73 m 2 with adequate sensitivity, especially if they are aged less than 70 [ 9 11 ]. Since eGFR measurement can detect more patients with renal dysfunction than questionnaires [ 12 ], with easier patient logistics and similar cost-effectiveness [ 13 , 14 ], many hospitals have adopted a policy of sCr measurements in all patients scheduled for intravenous (IV) CM and no longer use questionnaires for risk stratification or selection for eGFR measurement (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, the Choyke questionnaire may work well for the selection of patients to undergo serum creatinine [ 45 ]. However, many hospitals measure serum creatinine in all patients scheduled for intravenous ICM use since eGFR can detect more patients with kidney diseases than questionnaires [ 46 ]. On the other hand, many risk models and tools have been developed for PC-AKI prediction [ 33 , 36 , 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%